Making sense of teacher education in a globalising world: the distinctive contribution and challenges inherent in a socio-cultural approach - Burn, K; Menter, I (University of Chicago Press, 2021)
This article examines the potential of socio-cultural approaches for making sense of the way in which globalization shapes teacher education policy and practice in particular contexts. It argues that the value of such approaches lies in their re-framing of many conventional dualities that tend to characterize analyses of the process of globalization: dichotomies drawn, for example, between the global and the local, the micro and the macro, the material and the immaterial. It draws first on a tightly-focused study of a single teacher education program to outline central tenets of socio-cultural theory, before discussing aspects of a second, more wide-ranging, comparative study of the experience of learning to teach in different institutional and national contexts. The study has been chosen to illustrate how such theories illuminate the nested, interacting relationships between individuals’ social situations of development and the wider institutional, national and global contexts within which they are located.